Neurosensory Response of the Hand and Foot to Vibration Exposure - Marrone, Flavia; Sanna, Nicole; Sánchez García , Julio; Ronchese, Federico; Marchetti, Enrico; Tirabasso, Angelo; Bovenzi, Massimo; Tarabini, Marco (La Medicina del Lavoro, 2025)
Background: This study investigated the vibrotactile perception threshold (VPT) changes in the fingers and toes of twenty-eight healthy subjects (15 males and 13 females aged 20 to 62 years) exposed to hand- and foot-transmitted vibration. Methods: The VPT was measured before and after the exposure of the hands and feet to 5 minutes of triaxial white noise pseudorandom vibration. The post-vibration VPT was measured immediately after and 15 minutes after the end of the exposure to assess the temporary threshold shift (TTS) of vibration perception. The effects of the anatomical district (index finger and big toe), measurement time (before and after vibration exposure), test frequency (8, 31.5, and 125 Hz), age group (Under30s and Over 40s), and gender (male and female) on the changes in VPT were investigated. Results: The findings revealed that the index finger and the big toe exhibited comparable profiles in the vibrotactile sensitivity at the low-middle vibration frequencies and in the recovery of the perception threshold after vibration exposure. The big toe showed a higher perception threshold than the index finger, and the difference increased with the test frequency. In addition to vibration frequency, age and skin temperature influenced the results of VPT and TTS measurements. Conclusions: The findings of this study can contribute to outlining alternative frequency weighting functions for the neurosensory response of the hand and foot to vibration exposure, and to update the current guidelines for evaluating human vibration exposure.